Neuregulin-1 attenuates cognitive function impairments in a transgenic mouse model of Alzheimer’s disease - Jung‐Hee Ryu; B-H Hong; YJ Kim; E-J Yang; Moonseok Choi; Heebal Kim; Sangzin Ahn; T-K Baik; R-S Woo; Kim Hs (2016)
Abstract The neuregulin (NRG) family of epidermal growth factor-related proteins is composed of a wide variety of soluble and membrane-bound proteins that exert their effects via the tyrosine kinase receptors ErbB2-ErbB4. In the nervous system, the functions of NRG1 are essential for peripheral myelination, the establishment and maintenance of neuromuscular and sensorimotor systems and the plasticity of cortical neuronal circuits. In the present study, we report that an intracerebroventricular infusion of NRG1 attenuated cognitive impairments in 13-month-old Tg2576 mice, an animal model of Alzheimer’s disease (AD). In addition, according to Golgi-Cox staining, NRG1 rescued the reduction in the number of dendritic spines detected in the brains of Tg2576 mice compared with vehicle (PBS)-infused mice. This result was also corroborated in vitro as NRG1 attenuated the oligomeric amyloid beta peptide 1-42 (A β 1-42 )-induced decrease in dendritic spine density in rat primary hippocampal neuron cultures. NRG1 also alleviated the decrease in neural differentiation induced by oligomeric A β 1-42 in mouse fetal neural stem cells. Collectively, these results suggest that NRG1 has a therapeutic potential for AD by alleviating the reductions in dendritic spine density and neurogenesis found in AD brains.